2021
DOI: 10.1155/2021/8049516
|View full text |Cite
|
Sign up to set email alerts
|

Application of Adaptive Local Iterative Filtering and Permutation Entropy in Gear Fault Recognition

Abstract: In this paper, a fault identification method combining adaptive local iterative filtering and permutation entropy is proposed. The adaptive local iterative filtering can decompose the nonstationary signal into a finite number of stationary intrinsic mode functions. And the experiment gear fault data are decomposed into several intrinsic mode functions by this method. Then, using the permutation entropy to calculate each intrinsic mode function, it is found that the permutation entropy of the first several intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The execution time of system instructions is compensated with the transmission response time to eliminate the effect of fault diagnosis time difference. The system database is correlated and the information of data in the system is obtained, and the abnormal data is recorded by using the tagging function of the database [15][16]. At this point, the ratio between the correlation dimension and the abnormal data is greater than the preset criterion, indicating that the diagnostic region of the model is unstable and needs to be readjusted.…”
Section: Fft High Frequency Fault Diagnosis Model Designmentioning
confidence: 99%
“…The execution time of system instructions is compensated with the transmission response time to eliminate the effect of fault diagnosis time difference. The system database is correlated and the information of data in the system is obtained, and the abnormal data is recorded by using the tagging function of the database [15][16]. At this point, the ratio between the correlation dimension and the abnormal data is greater than the preset criterion, indicating that the diagnostic region of the model is unstable and needs to be readjusted.…”
Section: Fft High Frequency Fault Diagnosis Model Designmentioning
confidence: 99%
“…Zhang et al. applied ALIF to decompose gear fault signals into several IMFs and calculated the permutation entropy for each IMF and their grey correlation degree to identify fault types of gears [41]. They showed that this method can effectively diagnose gear faults.…”
Section: Vibration Signal Processing and Feature Extractionmentioning
confidence: 99%